2005
DOI: 10.1007/s11120-004-7080-2
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on the mechanism of photosynthetic water oxidation – dual role of oxo-bridges between Mn ions in (i) redox-potential maintenance and (ii) proton abstraction from substrate water

Abstract: Two mechanistic problems of photosynthetic water oxidation at the Mn complex of Photosystem II (PS II) are considered. (I) In the four Mn-oxidizing transitions, any pure Mn oxidation is predicted to cause an increase in redox potential that renders subsequent oxidation steps impossible (redox-potential problem). Formation of unprotonated oxo-bridges may counteract the potential increase. (II) The O-O formation step without any high-pK bases acting as proton acceptors is energetically unfavorable (acceptor-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 29 publications
(32 reference statements)
1
29
1
Order By: Relevance
“…In S 1 it is highly positive; approximately ϩ1 V (41). A potential increase upon the S 1 3 S 2 transition and a decrease in the S 0 * state is anticipated (41,42); the potential of the Mn II 4 state presumably is comparably low (Յ0 V) (43,44). That electrophilic centers are the primary target for reduction by electrons liberated because of x-ray exposure is also supported by investigations on protein crystals where disulfide bridges first became reduced at 100 K (18,19) and by EPR results (Ref.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In S 1 it is highly positive; approximately ϩ1 V (41). A potential increase upon the S 1 3 S 2 transition and a decrease in the S 0 * state is anticipated (41,42); the potential of the Mn II 4 state presumably is comparably low (Յ0 V) (43,44). That electrophilic centers are the primary target for reduction by electrons liberated because of x-ray exposure is also supported by investigations on protein crystals where disulfide bridges first became reduced at 100 K (18,19) and by EPR results (Ref.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, the native S 0 as created by light flash application at room temperature may contain one Mn(-O) 2 Mn and one Mn(-O)(-OH)Mn unit (4,7). At room temperature the S 0 3 S 1 transition is electroneutral (65,66); probably the manganese oxidation is coupled to deprotonation of a -OH bridge (7,36,42). At the cryogenic temperatures where the S 1 3 S 0 * step occurred, charge-compensating long-range proton movements are unlikely so that protonation is impaired, and instead the -O bridge is broken.…”
Section: Discussionmentioning
confidence: 99%
“…All these factors are beneficial for improving the photocurrents. In this composite photoanode, photon absorption and redox catalysis are separated, which is similar to the photosystem II [21].…”
Section: Resultsmentioning
confidence: 99%
“…[92] previously concluded that O(H)-bridged metal centers are a candidate for a common structural motif in multinuclear WOCs. The O(H) bridges may have an essential role in reducing the overpotential for water oxidation by redox-potential leveling; that is, the maintenance of an approximately constant redox potential for the four sequential oxidation steps assumed to occur before O 2 formation, as discussed in more detail in reference [93][94][95]. This redox leveling could be facilitated on the atomic scale by coupling of -OH deprotonation to the oxidation step, possibly in close analogy to processes in PSII [91].…”
Section: Figure 93 (A) Ideal Layered Oxide/hydroxide and Analogous Smentioning
confidence: 99%